2012
DOI: 10.1177/039139881203501207
|View full text |Cite
|
Sign up to set email alerts
|

Late de Novo Aortic Regurgitation with the Jarvik 2000 Flowmaker® left ventricular assist device

Abstract: Introduction There is a worldwide trend towards a more liberal use of ventricular assist devices (VADs) as a definitive treatment for patients in end-stage heart failure. This has also led to a new set of complications related to the prolonged interaction between the native heart and the device. Methods We report a case of, late, de novo aortic regurgitation (AR), leading to acute pulmonary edema in a 56-year-old man, 20 months after the implantation of a left ventricular assist device (LVAD), the Jarvik 2000 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…The progression of AI during cf-LVAD support may negatively impact the patients' clinical outcomes; the aggravation of the continuous retrograde flow loop can cause severe restriction of forward blood circulation and induce malperfusion of the vital organs [1]. In view of minimizing these adverse effects, recent studies have suggested reducing the LVAD pump speed to promote aortic valve opening, as progressive AI has been consistently shown to associate with a closed aortic valve [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. In this context, LVADs that are equipped with the ILS technology, which facilitates aortic valve opening, may have the potential to prevent AI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The progression of AI during cf-LVAD support may negatively impact the patients' clinical outcomes; the aggravation of the continuous retrograde flow loop can cause severe restriction of forward blood circulation and induce malperfusion of the vital organs [1]. In view of minimizing these adverse effects, recent studies have suggested reducing the LVAD pump speed to promote aortic valve opening, as progressive AI has been consistently shown to associate with a closed aortic valve [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. In this context, LVADs that are equipped with the ILS technology, which facilitates aortic valve opening, may have the potential to prevent AI.…”
Section: Discussionmentioning
confidence: 99%
“…With accumulating evidence that AI occurs more frequently in patients with a persistently closed aortic valve during cf-LVAD support [1][2][3][4][5][6][7][8][9][10], strategies to prevent AI have now focused on the optimization of the pump speed to promote aortic valve opening [1,2,[4][5][6][7][8][9][10][11][12][13][14][15]. In some cf-LVADs, including the HeartWare HVAD (HeartWare, Inc., Framingham, MA, USA), the HeartMate III (Abbott Laboratories, Abbott Park, IL, USA), and the Jarvik 2000 (Jarvik Heart Inc., New York, NY, USA), the devices are equipped with a function that facilitates intermittent aortic valve opening by periodically minimizing pump flow.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, different complications related to the loss of pulsatility and to the prolonged interaction between the human body and the mechanical device (e.g. late aortic regurgitation, infections, hemolysis, thromboembolic events and acquired bleeding disorders) remain high, which might jeopardize the long-term duration of the LVAD therapy [2][3][4][5]. Many of these complications are related to hemodynamic changes, such as modification on flow rate, that can cause recirculation or stagnation areas, and shear stress pattern, that influences the atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…This cyclic speed change is designed to decrease potential areas of blood stasis and to promote intermittent aortic valve opening. The Jarvik 2000 uses an intermittent low-speed (ILS) cycle to allow for conditions promoting aortic valve opening (14). The ILS cycle slows the pump speed to 6000 rpm once each minute for 8 s, before returning to the original set speed.…”
Section: Discussionmentioning
confidence: 99%